2013
DOI: 10.1007/s10278-013-9642-3
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Symptoms Amongst Clinical Radiologists and the Implications of Reporting Environment Ergonomics—A Multicentre Questionnaire Study

Abstract: This multicentre study aimed to assess compliance of the reporting environment with best ergonomic practice and to determine the prevalence of musculoskeletal symptoms related to working as a radiologist. All 148 radiology trainees and consultants in 10 hospitals across the region were invited to complete a musculoskeletal symptoms and reporting ergonomics questionnaire. Best ergonomic reporting practice was defined, following literature review, as being able to alter the following: monitor, desk, chair and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Some studies have addressed ergonomic strategies to reduce musculoskeletal symptoms among radiologists. Rodrigues et al demonstrated a high prevalence of musculoskeletal symptoms in radiology workstations that show poor compliance with ergonomic best practices [40]. Boiselle et al showed that although musculoskeletal symptoms are highly prevalent among radiologists, ergonomic interventions can effectively reduce these symptoms [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have addressed ergonomic strategies to reduce musculoskeletal symptoms among radiologists. Rodrigues et al demonstrated a high prevalence of musculoskeletal symptoms in radiology workstations that show poor compliance with ergonomic best practices [40]. Boiselle et al showed that although musculoskeletal symptoms are highly prevalent among radiologists, ergonomic interventions can effectively reduce these symptoms [18].…”
Section: Discussionmentioning
confidence: 99%
“…For example, around 25% of radiologists in our study reported never making personal adjustments of workstation height despite an adjustable workstation. One study reported that radiologists with good knowledge of ergonomics experienced significantly less lower back pain compared to those with poor knowledge [40]. Furthermore, the same study demonstrated that even where certain facilities were available, less than a third of radiologists made personal adjustments prior to a reporting session.…”
Section: Discussionmentioning
confidence: 99%
“…FMLA leave may be needed by the radiologist for chronic mental health conditions such as burnout [12], depression [13], and impairment [14]. Radiologists may need FMLA for chronic work-related physical conditions such as repetitive stress injury [15,16] and cataracts [17,18]. Alternatively, chronic physical conditions likely unrelated to work, such as multiple sclerosis, cardiovascular disease, stroke, and cancer, may precipitate the need for a leave of absence under FMLA.…”
Section: Discussionmentioning
confidence: 99%
“…Good ergonomic knowledge is of paramount importance. A previous study reported that radiologists with good ergonomic knowledge experienced significantly less lower back pain than did those with poor knowledge [22].…”
Section: Robertson Et Al Conducted An Analysis Of the Work Environmementioning
confidence: 94%